Trace DNA recovery rates from firearms and ammunition as revealed by casework data. Issue 1 (2nd January 2023) - Prasad, Elisha; Atwood, Lauren; van Oorschot, Roland A. H.; McNevin, Dennis; Barash, Mark; Raymond, Jennifer
ABSTRACT: Understanding casework DNA recovery rates per evidence type is crucial for advancing forensic methodologies and practices. This study assesses DNA recovery and profile data for 17 firearm parts (including cartridges, bullets and cases: CBCs) using New South Wales firearms casework data from 2015 to 2019. CBCs were further classified as shotgun or metallic cartridges and as unfired or fired. Quantitative data analysis showed that the least DNA was recovered from the hammer, safety and CBCs, while a single swab of multiple firearm parts resulted in the highest DNA recovery. Shotgun and unfired cartridges yielded more DNA than metallic and fired cartridge cases, respectively. Additionally, DNA collected from exhibits after fingerprinting yielded more DNA than exhibits sampled for DNA without any fingerprint examination. Profile data analysis showed that at least 64% of samples were unusable in casework. Cumulatively swabbed areas were most likely to produce usable profiles. Up to 22% and 38% of usable and unusable profiles, respectively, were mixed. Internal parts of the firearms had lower percentages of mixed profiles. The results from the data suggest the areas to prioritize for DNA recovery from firearms and highlights the need for further research to improve sample collection from firearms and ammunition.